SIKAPGURU DI DAERAH ISTIMEWA YOGYAKARTA TERHADAP PENGEMBANGAN PROFESI - Sukidjo, Sukidjo (Jurnal Cakrawala Pendidikan, 2004)
Nowadays, many yunior and senior high school teachers who have achieve "guru Pembina" IVa rank face a difficulty to get promotion to IV b rank and above. This occurs since to get promotion to IVb rank and above, they must have 12 credit points ofprofession development. They are little know about profession development. The purpose ofthis stud~are: to know degree ofcomprehension, degree ofdifficulty, and yunior and senior high school teacher's attitude to'profession development. The population ofthis study are juniorand senior high school teachers in Yogyakarta Special Territory. Multistage random sampling is employed in this study. Data collection methods are quesioner, documentation, and interview while data collecting instrument is quesioner. Data analysis methods used are differentiation and correlation technique using SPSS 10.0 Based on data analysis, some conclusion can be dra\VTI. Firstly, 58% of teachers have low degree ofcomprhension, 80% ofteachers have moderate degree ofdifficulty and 69% ofteachers have low attitude to profession development. Secondly, there is no significant difference in teacher's attitude to profession development between teachers holding graduate and under graduate degree, junior and senior high school teachers, III rank and IV rank teachers and who have everjoined in training course and who have not everjoined. Thirdly, here is significant difference in degree ofcomprehention ofprofession development between teachers holding graduate and under graduate degree. Fourtly, there is no significant correlation between degree ofcomprehention and degree of difficulty with attitude to profession development. Fifthly, there is negative correlation and significant between